Women's voices made visible: photovoice in visual criminology - Fitzgibbon, Wendy (Punishment & society, 2018)
The voices of women subject to the criminal justice system are often ignored and unheard. This article considers the effectiveness of photovoice, a form of participatory photography research, as a visual method of enabling and communicating marginalised women’s experiences in criminological research. By utilising the potentially empowering technique of photovoice in two research projects, the narratives of women who inject drugs in Hungary and women who have experienced supervision in England are conveyed through their own participant-generated photographs. These images convey the pains and aspirations of the participants' lives and show how photovoice is a useful method for visual criminological research and exposes the shared problems faced by two vulnerable populations across two countries in Europe.